2016
DOI: 10.18632/oncotarget.13164
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a seven-miRNA signature as prognostic biomarker for lung squamous cell carcinoma

Abstract: BackgroundSpecific biomarkers for outcome prediction of lung squamous cell carcinoma (LUSC) are still lacking. This study assessed the prognostic value of differentially expressed miRNAs of LUSC patients.ResultsTwelve of the 133 most significantly altered miRNAs were associated with overall survival (OS) across different clinical subclasses of the Cancer Genome Atlas (TCGA) LUSC cohort. A linear prognostic model of seven miRNAs was developed to divide patients into high- and low-risk groups. Patients assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…MiRNAs are important in the occurrence and development of LC [43][44][45][46][47][48]. Recent studies reported that dysregulation of the expression of multiple miRNAs, including miR-182-5p, was significantly correlated with tumorigenesis of LC [34].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are important in the occurrence and development of LC [43][44][45][46][47][48]. Recent studies reported that dysregulation of the expression of multiple miRNAs, including miR-182-5p, was significantly correlated with tumorigenesis of LC [34].…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [ 18 ] investigated whether microRNA expression profiles can predict clinical outcome of NSCLC patients using real-time RT-PCR and identified a five-microRNA signature for the prediction of treatment outcome of NSCLC, which is an independent predictor of the cancer relapse and survival of NSCLC patients. Recently, Gao et al [ 19 ] reported that seven-miRNA signature may have clinical implications in the outcome prediction of lung squamous cell carcinoma (LUSC). Of these 7 miRNAs, 2 (hsa-mir-139, hsa-mir-326) were negatively correlated with survival, while the other 5 (miR-101-2, miR-182, miR-183, miR-190, hsa-miR-944) were protective.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of LUSC is complex, and the prognosis of LUSC cannot be adequately explained by a single gene. In addition, although, in several studies, more than one gene was identified, the signatures were diverse. This has resulted in application difficulties and challenges in clinical practice because selecting the best signature is not an easy task.…”
Section: Introductionmentioning
confidence: 99%